Wombat waiting - Applegate, Katherine (Storytide, an imprint of HarperCollins Publishers, 2026)
Wombat isn't actually a wombat--but when the homeless dog is discovered, singed and ash-covered after a terrible fire destroys a community, someone tags her with the nickname and it sticks. Wombat is a "destiny dog." Something inside of her (she nicknames it "Voice') keeps telling her there's a special someone out there who is meant to be her person. Surrounded by a devastated town, Wombat takes up residence on bench near the makeshift community center, an old brick warehouse that, for the most part, survived the flames. A small part of the community center evacuation site has been repurposed for the local wildlife rehab sanctuary that burned down. All of the animals were spared, and the temporary quarters include an elderly fruit bat and a young Northern saw-whet owl. No matter what, Wombat refuses to move from her perch, despite the efforts of many humans. Clearly the dog is waiting for someone. But for whom? And what are the odds they survived?